Il giornalismo come riscrittura: considerazioni sul ruolo del comunicato stampa (Altre Modernità, 2012)
This paper addresses the topic of rewriting in journalistic discourse by examining the typical textual features of the press release, one of the most commonly used journalistic sources. Journalism has long being recognised as being based on reproductive writing practices (Jakobs 2003), as it consists, as Bell (1991: 41) puts it, “of previously composed text reworked into text news”. In this process of rewriting, a key role is played by sources. While their use (and occasional manipulation) on the part of journalists has been variously explored in the literature, less has been done to investigate the textual features of documents specifically designed to serve as sources, most notably press releases. The paper provides a description of the characterising features of the genre of the press release, highlighting the essentially “preformulated” nature (Jacobs 1999) of these documents, i.e. the fact that their formal traits, as well as the structuring of their content, are strategically designed to facilitate reproduction. The paper concludes that while the re-use of textual material from sources is a crucial aspect of journalistic text production, care should be taken to distinguish between rewriting and uncritical textual reproduction: although recourse to the latter has been growing exponentially over the last decade due to an increasing shortening of news production cycles that has turned journalists into “processors rather than generators of news” (Lewis et al. 2008: 27) under constant pressure to continuously “churn out” (Davis 2008) stories, a renewed attention to rewriting as a key component of journalistic text production practices should be encouraged.
Keywords: riscrittura; discorso giornalistico; comunicato stampa; genre analysis; entestualizzazione